The characterisation by liquid chromatography of lake pigments prepared from European buckthorn (Rhamnus cathartica L.) - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2012)
Purpose - The purpose of this paper is to prepare, analyse and measure the colour values of the lake pigments obtained from the reaction of Al3 +, Fe2 + and Sn2 + metal salts with the natural dyes present in European buckthorn (Rhamnus cathartica L.). Design/methodology/approach - A reversed-phase high performance liquid chromatography (HPLC) with diode-array detection method was utilised for the identification of buckthorn lake pigments. The extraction of dyes from the lake pigments was carried out with 37% hydrochloric acid/methanol/water (2:1:1; v/v/v) solution. Findings - According to the results of the HPLC analysis of the lake pigments, it was determined that rhamnetin, kaempferol, and emodin were present in the acid hydrolysed plant extract and in the lake pigment that was precipitated by Sn(II), quercetin-3-arabinosid, rhamnetin, and emodin were present in the non-hydrolysed plant extract, and kaempferol, rhamnetin, isorhamnetin, and emodin were found in the lake pigment that was precipitated by AI(III). Rhamnetin and emodin were present in the lake pigment that was precipitated by Fe(II). Research limitations/implications - In the present context for the preparation of buckthorn lake pigments, a simple and practical method is presented. In addition, the analysis of the lake pigments was performed by reversed phase HPLC (RP-HPLC) with diode array detector (DAD). Practical implications - The paper describes the preparation of lake pigments and their qualitative analysis. This method can be used to determine the origins of the dyestuffs used in historical art pieces. Originality/value - The paper describes the development of methods for the analysis and the preparation of European buckthorn lake pigments.
Keywords: Dyes; Pigments; Colours technology; Lake pigments; European buckthorn; Natural dye; Mordant; High performance liquid chromatography; NATURAL PIGMENTS; COLORING MATTERS; HPLC ANALYSIS; IDENTIFICATION; DYES; EXTRACTION; DYESTUFFS